2016
DOI: 10.1136/bmjopen-2015-010352
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for validity of a national physician and patient-reported, cross-sectional survey in China and UK: the Disease Specific Programme

Abstract: ObjectiveDiabetes represents a significant challenge for Chinese healthcare providers. Healthcare decision-making is generally based on many data sources, including randomised controlled and real-world studies; however, good-quality data from Chinese diabetes patients are scarce. We performed an initial validation to assess the representativeness of one source of real-world data—the Diabetes Adelphi Disease Specific Programme (DSP) in China.SettingChina, UK.ParticipantsThe Chinese DSP included 2060 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(75 citation statements)
references
References 10 publications
0
75
0
Order By: Relevance
“…DSP surveys use validated methods to generate data from clinical practice regarding treatment practices, resource use, and quality of life. 10,11 The Lupus DSP is conducted at regular intervals (previously in 2010 and 2013), and it also collected data from nephrologists and their patients with lupus nephritis; here, we focus on rheumatologists and patients with SLE. The LPP used specific sections of the previous Lupus DSP survey, and both surveys were developed by ARW independent of GlaxoSmithKline (GSK), using the Adelphi Disease Specific Programme method.…”
Section: Methodsmentioning
confidence: 99%
“…DSP surveys use validated methods to generate data from clinical practice regarding treatment practices, resource use, and quality of life. 10,11 The Lupus DSP is conducted at regular intervals (previously in 2010 and 2013), and it also collected data from nephrologists and their patients with lupus nephritis; here, we focus on rheumatologists and patients with SLE. The LPP used specific sections of the previous Lupus DSP survey, and both surveys were developed by ARW independent of GlaxoSmithKline (GSK), using the Adelphi Disease Specific Programme method.…”
Section: Methodsmentioning
confidence: 99%
“…Data used for this analysis are more likely to provide a representative, real-world sample of patients with T2DM and real-world patient behavior than randomized clinical trial data. 10 , 22 For example, in clinical trials, <5% of patients discontinued a GLP1 RA due to GI effects; however, higher rates, between 5% and 10%, have been observed in clinical practice. 23 , 24 Clinical trials have reported the most common AEs with GLP1 RAs to be GI events, including diarrhea, nausea, and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected using the Adelphi Prostate Cancer Disease Specific Programme (DSP), an independent, multi-country, cross-sectional survey. Details of the full DSP methodology have previously been described [25], [26], [27]. The Adelphi DSPs do not have any academic or pharmaceutical affiliations.…”
Section: Methodsmentioning
confidence: 99%